Literature Review: Strategi Efektif untuk Mengembangkan Komunikasi pada Anak dengan Hambatan Majemuk - Swarna Dyah Puspita, Andhini; Maulidah, Siti; Kiarra Latisha, Erva; Nurmalinda, Rossa; Taboer, Mohammad Arif; Maulidina, Citra Ashri (Universitas Negeri Jakarta, 2024)
Parents and educators need special strategies to optimize an effective way to develop communication skills in children with multiple disability. This article aims to find out how to effectively develop the communication skills of children with multiple disability that have been researched by experts both from Indonesia and abroad. The method used by researchers in the preparation of this article is literature review, which is a method by collecting data from relevant references related to communication skills strategies for children with multiple disability. And the findings of this article will provide a comprehensive picture in developing communication for children with multiple disability verbally and non-verbally to the existing interactive media. However, there is still a need for further research that aims to increase understanding and support for the role of parents and educators in the development of communication in children with multiple disability.